2016
DOI: 10.1038/srep23638
|View full text |Cite
|
Sign up to set email alerts
|

Morphotype-specific effector functions of Cryptococcus neoformans PUM1

Abstract: The basidiomycete fungal pathogen Cryptococcus neoformans requires the PUF protein, Pum1, for hyphal morphogenesis during sexual development. In this study we found that Pum1 was auto-repressive under growth as yeast, but that auto-repression was relieved during filamentous growth through utilization of an alternative transcription start site driven by the master filamentation regulator Znf2. In addition, Pum1 was required to stabilize the ZNF2 mRNA through an indirect mechanism suggesting that Znf2 and Pum1 e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 19 publications
0
18
0
Order By: Relevance
“…Instead, the coordination of the meiotic cycle and basidial differentiation may potentially be attributed to integrated control by a shared regulatory program that orchestrates these events. Our previous study has shown that the Pumilio family RNA binding protein Pum1 is important for the expression of the meiosis protein Dmc1 and post-meiotic sporulation ( Wang et al, 2014 ; Kaur and Panepinto, 2016 ). This suggested us to test whether Pum1 is also involved in basidial maturation.…”
Section: Resultsmentioning
confidence: 99%
“…Instead, the coordination of the meiotic cycle and basidial differentiation may potentially be attributed to integrated control by a shared regulatory program that orchestrates these events. Our previous study has shown that the Pumilio family RNA binding protein Pum1 is important for the expression of the meiosis protein Dmc1 and post-meiotic sporulation ( Wang et al, 2014 ; Kaur and Panepinto, 2016 ). This suggested us to test whether Pum1 is also involved in basidial maturation.…”
Section: Resultsmentioning
confidence: 99%
“…Yet alternative splicing has been shown to poorly influence proteome diversity and appears to be more a means to finely tune gene expression in response to environmental cues (41). In contrast, several examples of regulated alternative start sites have been described suggesting that this mechanism might represent a major means to diversify the proteome in fungi (47,48). This suggests that an important part of the proteome is still not described in this kingdom.…”
Section: Fungal Genomics: a Revolution In The Study Of Fungal Pathogensmentioning
confidence: 99%
“…reporter transcription was then inhibited by the removal of galactose through washing with and 146 resuspension in YNB with 2% dextrose with and without H2O2. Northern blot analysis was 147 performed and imaged using 5 µg of RNA as previously described (17). The hybridized 148 transcript signal was normalized to rRNA gel bands.…”
Section: Stability Assays and Northern Blot Analysismentioning
confidence: 99%